2014
DOI: 10.11648/j.ijnfs.20140306.13
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Adolescents in Selected Government and Private Secondary Schools of Addis Ababa, Ethiopia

Abstract: Background: Changes in the nutritional intake combined with increasingly sedentary life styles and increasing urbanization has led to the emergence of chronic disease as a major new health threat. Objective: To assess and compare nutritional status of adolescents and analyze the risk factors associated to/with overweight/obesity in government and private secondary schools of Addis Ababa, 2012. Methods: A comparative cross sectional study comprising 1024 adolescents of government and private secondary schools o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(87 citation statements)
references
References 21 publications
(23 reference statements)
7
69
9
Order By: Relevance
“…This study showed that 32.2% of school adolescent girls were underweight. This magnitude is higher as compared to other studies conducted in Arsi Zone ( [8,[12][13][14][15][16][17][18][19][20][21][22][23][24]. This might be due to the low socioeconomic status in this study area.…”
Section: Discussioncontrasting
confidence: 55%
“…This study showed that 32.2% of school adolescent girls were underweight. This magnitude is higher as compared to other studies conducted in Arsi Zone ( [8,[12][13][14][15][16][17][18][19][20][21][22][23][24]. This might be due to the low socioeconomic status in this study area.…”
Section: Discussioncontrasting
confidence: 55%
“…7,34,35 The present study shows that the prevalence of thinness is higher than those findings from Tunisia (1.3%), 6 Arba Minch-South-Ethiopia (8%), 9 and Addis Ababa City (6.2%). 10 Undernutrition varies from region to region depending on ecological, social, economic, and other factors. In Ethiopia, at present, the most serious nutritional problems are mainly due to low socioeconomic status, inadequate diversity foods, and poor water supplies.…”
Section: Discussionmentioning
confidence: 99%
“…8 Studies done in Arba Minch area of Southern Ethiopia and Addis Ababa, capital city of Ethiopia, reported that the prevalence of thinness was 8% and 6.2%, respectively. 9,10 Similar research conducted in National School Health and Nutrition (SHN) in 2008 showed that the prevalence of thinness was 23%. 11 Socioeconomic status, place of residency, age, family size, maternal education, poor water supply & sanitation, diarrhea episodes, and eating less than three meals per day were the frequently mentioned factors that influence the nutritional status of the children.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Home environment matters a lot as there are no facilities for girl's adolescents for different activities to perform in the home they spend their little bit time on household activities like cooking, washing, ironing, cleaning of house etc. It was studied that Saudi adolescents and conclude that there were very less opportunities for female adolescents as their parents do not provide an environment for physical activities that's why they were physically inactive [8][9][10][11][12][13][14][15].…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%